2019
DOI: 10.3389/fchem.2019.00839
|View full text |Cite
|
Sign up to set email alerts
|

Current Applications of Gas Sensor Based on 2-D Nanomaterial: A Mini Review

Abstract: Gas sensor, as one of the most important devices to detect noxious gases, provides a vital way to monitor the concentration and environmental information of gas in order to guarantee the safety of production. Therefore, researches on high sensitivity, high selectivity, and high stability have become hot issues. Since the discovery of the nanomaterial, it has been increasingly applied to the gas sensor for its distinguishing surface performances. However, 0-D and 1-D nanomaterials, with limited electronic confi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
45
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(46 citation statements)
references
References 58 publications
0
45
0
1
Order By: Relevance
“…Studies have shown that in addition to traditional layered 2D nanomaterials such as graphene, black phosphorus or phosphorene, silicene, borophene, boron nitride, and transition metal dichalcogenides (TMDs), metal oxides may also have 2D structures [351,355]. It was established that some metal oxides such as Ga 2 O 3 and metal trioxides with a general formula of MO 3 (M = Mo, Ta, W, etc.)…”
Section: Features Of 2d Nanomaterials Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that in addition to traditional layered 2D nanomaterials such as graphene, black phosphorus or phosphorene, silicene, borophene, boron nitride, and transition metal dichalcogenides (TMDs), metal oxides may also have 2D structures [351,355]. It was established that some metal oxides such as Ga 2 O 3 and metal trioxides with a general formula of MO 3 (M = Mo, Ta, W, etc.)…”
Section: Features Of 2d Nanomaterials Synthesismentioning
confidence: 99%
“…Currently, based on these 2D nanomaterials, a large number of prototypes of gas sensors have been made, which have increased sensitivity to various gases. An analysis of these results can be found in numerous reviews devoted to the consideration of these materials [323,326,334,345,[347][348][349][350][351][352][353][354].…”
mentioning
confidence: 99%
“…For many years, how to measure and monitor the relative humidity (RH) amount has been a matter of debate in different industries, agriculture, and social health [1][2][3] . For examples, nano-based gas sensors provide signi cant approach to assess the concentration and environmental information of gases 4,5 . In fact, these sensors comprise of a transducer and an active layer to convert the chemical information into another form of electrical signal gradients like frequency, current, voltage, etc.…”
Section: Introductionmentioning
confidence: 99%
“…The use of nanomaterials has been shown to improve traditional sensing techniques in terms of sensitivity, stability, response time, and selectivity [ 18 ]. The aforementioned benefits of nanomaterials are often ascribed to their high surface to volume ratio, high surface energy, quantum size effect, and high electron conductivity [ 19 ].…”
Section: Introductionmentioning
confidence: 99%